TRANSFORMING ELEMENTARY SCHOOL TEACHERS’ COMPETENCE THROUGH DEEP LEARNING TRAINING IN THE MERDEKA CURRICULUM - Mansurdin; Dina Amsari; Leni Zahara; Tiok Wijanarko; Reinita; Masniladevi; Ummiatul Fitri; Aissy Putri Zulkarnaini (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program supported the implementation of a deep learning approach in the Merdeka Curriculum to develop eight graduate profiles characterized by critical, creative, and adaptive thinking. Many elementary school teachers in Kecamatan V Koto Kampung Dalam, Pariaman City, still lacked a solid understanding of deep learning concepts and implementation strategies, including limited digital literacy, which affected learning quality. The program aimed to strengthen teachers’ competencies in designing and applying deep learning-based instruction aligned with the eight graduate profiles. Participatory Action Research (PAR) was used through stages of problem identification, planning, training, observation, and reflection. Participants were sixth-grade teachers from 31 public elementary schools in the target area. Results showed a significant improvement in teachers’ understanding, indicated by higher post-test scores compared to pre-test scores. In the post-test, 65% of participants achieved perfect scores and the rest obtained very good results. Follow-up mentoring further enhanced teachers’ skills in developing deep learning-based teaching modules. Overall, the training effectively improved teacher professionalism and contributed to better learning quality in elementary schools.